Association of dietary intake of theobromine with periodontitis: NHANES 2009–2014 - Ya-Shi Zhou; Song Cai; Si-Yu Li; Miao Shu; Ben Qin; Ju-Kun Song; Ju-Xiang Peng (BMC Oral Health)
Abstract Background Theobromine intake usually comes from coffee, tea, and cocoa foods. Related studies have shown that theobromine is a bioactive molecule with anti-inflammatory, antithrombotic, anti-fat, and other effects. Periodontitis is a kind of oral inflammatory disease with high incidence, which is characterized by alveolar bone resorption leading to tooth loosening and loss. Therefore, this study aims to investigate whether theobromine intake correlates with periodontitis and whether it is a risk or protective factor for periodontitis. It hopes to provide a basis for theobromine-related diet or drugs to prevent and treat periodontitis. Methods The study employed a cross-sectional design and utilized data from the National Health and Nutrition Examination Survey (NHANES) collected between 2009 and 2014. The exposure factor was theobromine intake, derived from two-day, 24-hour total nutrient intake data from dietary data. Periodontitis-related indicators as outcome factors were derived from the oral health component of the examination data. We used weighted multiple logistic regression, fractional Response Model, subgroup analysis, and the effect moderation test to explore the relationship between theobromine dietary intake and periodontitis severity based on weighting and adjusting for confounding factors. Results After adjusting for relevant confounding factors, weighted logistic regression showed that theobromine intake was negatively correlated with periodontitis-related indicators (mean periodontal pocket depth, mean clinical attachment loss, and the percentage of sites with PD ≥ 4 mm). And theobromine intake was positively correlated with the number of teeth. Conclusion This study demonstrated theobromine intake may serve as a protective factor against the development of periodontitis.